Semi-Generalized Closed Set in the Closure Spaces - et. al., Dr. Neeran Tahir Abd Alameer , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we introduce the concept of semi generalized closed set (=